# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime }+4 y = 3 \delta \left (t -1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-5 y = 2 \,{\mathrm e}^{-t}+\delta \left (t -3\right )
\] |
✓ |
✓ |
|
\[
{}5 x y+4 y^{2}+1+\left (x^{2}+2 x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x \tan \left (y\right )+\left (x -x^{2} \tan \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (x^{2}+1\right )+y+\left (2 x y+1\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}4 x y^{2}+6 y+\left (5 x^{2} y+8 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}5 x +2 y+1+\left (2 x +y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x -y+1-\left (6 x -2 y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -2 y-3+\left (2 x +y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}6 x +4 y+1+\left (4 x +2 y+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x -y-6+\left (x +y+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +3 y+1+\left (4 x +6 y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y = y^{\prime }+\frac {{y^{\prime }}^{2}}{2}
\] |
✓ |
✓ |
|
\[
{}\left (-x y^{\prime }+y\right )^{2} = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y-x = {y^{\prime }}^{2} \left (1-\frac {2 y^{\prime }}{3}\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x \left (y-1\right )+\left (y-1\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-x^{5}+\sqrt {x}
\] |
✓ |
✓ |
|
\[
{}3 y-2 x +\left (3 x -2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+x -1+\left (2 x y+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{2 y}+\left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }-x^{2} y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y-2 x}{x}
\] |
✓ |
✓ |
|
\[
{}x^{3}+y^{3}-y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = x^{2}+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \tan \left (x \right ) = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x -2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{2}+y^{2}}{2 x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{-y}+\left (x^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 y = {\mathrm e}^{3 x}+{\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x +\frac {1}{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = \left (3 x +2\right ) {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}2 \sin \left (3 x \right ) \sin \left (2 y\right ) y^{\prime }-3 \cos \left (3 x \right ) \cos \left (2 y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = \left (1+x \right ) \left (1+y\right )
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x -y}{y+2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 x -y+1}{3 y-x +5}
\] |
✓ |
✓ |
|
\[
{}3 y-7 x +7+\left (7 y-3 x +3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +\left (2-x +2 y\right ) y^{\prime } = x y \left (y^{\prime }-1\right )
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime }+y \sin \left (x \right ) = 1
\] |
✓ |
✓ |
|
\[
{}\left (y^{2}+x \right ) y^{\prime }+y-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \tan \left (x \right ) = \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \ln \left (x \right ) = x^{-x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+n y = x^{n}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-n y = x^{n}
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+x \right ) y^{\prime }+y = x
\] |
✓ |
✓ |
|
\[
{}\cot \left (x \right ) y^{\prime }+y = x
\] |
✓ |
✓ |
|
\[
{}\cot \left (x \right ) y^{\prime }+y = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\tan \left (x \right ) y^{\prime }+y = \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\tan \left (x \right ) y^{\prime } = y-\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime }+y = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \sin \left (x \right ) = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }+y = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}\sqrt {x^{2}+1}\, y^{\prime }+y = 2 x
\] |
✓ |
✓ |
|
\[
{}\sqrt {x^{2}+1}\, y^{\prime }-y = 2 \sqrt {x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}\sqrt {\left (x +a \right ) \left (x +b \right )}\, \left (2 y^{\prime }-3\right )+y = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {\left (x +a \right ) \left (x +b \right )}\, y^{\prime }+y = \sqrt {x +a}-\sqrt {x +b}
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime } y^{2} = 2 x -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 6 x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{y} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sec \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \cos \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {4 x y}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{x^{2}-1}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}\cot \left (x \right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{-2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = 2 x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x y+y
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+1\right ) y^{\prime } = 3 x^{2} \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x \cos \left (y\right ) y^{\prime } = 1+\sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y \left (y-1\right )
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } = 1-y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime } = x y
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime } = \left (x^{2}+1\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x} \left (1+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y} y^{\prime }+2 x = 2 x \,{\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y \,{\mathrm e}^{2 x} y^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}\left (x +y-1\right ) y^{\prime } = x -y+1
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = 2 x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2}-y^{2}+x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-2 x y-2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 3 \left (x^{2}+y^{2}\right ) \arctan \left (\frac {y}{x}\right )+x y
\] |
✓ |
✓ |
|
\[
{}x \sin \left (\frac {y}{x}\right ) y^{\prime } = y \sin \left (\frac {y}{x}\right )+x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+2 \,{\mathrm e}^{-\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x +y\right )^{2}
\] |
✓ |
✓ |
|